Click yes to consent: Acceptability of incorporating informed consent into an internet-based testing program for sexually transmitted and blood-borne infections. (September 2017) - Gilbert, Mark; Bonnell, Amanda; Farrell, Janine; Haag, Devon; Bondyra, Mark; Unger, David; Elliot, Elizabeth
Highlights: This manuscript describes an approach for translating clinical practices for achieving informed consent into the navigation path of a publicly-funded internet-based testing service for sexually transmitted and blood-borne infections (i.e., where clients are tested without interacting with a health care provider). This has not been previously described in the literature to our knowledge; discussion of informed consent with respect to online health services has focused on commercial direct-to-consumer genetic testing. In interviews, potential users of the service valued the formal consent process developed as it reflects concern for the patient, although this may be influenced by prior testing and lived experience. We found that website design features can disrupt speedy click-through and the routinization of informed consent (e.g., click-through without reading terms), and are directly related to patient perceptions of the value of the consent step. Abstract: Background: Autonomous use of online health care services without interaction with a health care provider challenges existing models for achieving informed consent (IC); current examinations of this issue have focused on commercial direct-to-consumer genetic testing. As IC is integral to publicly funded clinical testing services, we incorporated pre-test concepts necessary for IC in GetCheckedOnline (GCO), British Columbia's online sexually transmitted and blood-borne infection (STBBI) testing service. Objective: We assessed the acceptability of this IC step and its design options among potential users during usability testing of GCO. Methods: English-speaking participants ≥ 19 years were recruited from Craigslist and among provincial STI clinic clients for usability testing of an early version of GCO, which included a consent webpage presenting 8 pre-test statements for review prior to completing testing. Participants were interviewed regarding their acceptability, perceptions, and understanding of the consent page; transcripts were analyzed thematically. Results: We conducted 13 interviews (9 males, 4 females; 9 self-identified as heterosexual; all had previously tested for STBBI). We identified three main themes: i) the meaning of IC (consent page viewed as important and for protection of individual and organization; participants demonstrated varying understandings of specific components); ii) the impact of previous experience on understanding IC (participants understood difference between online and in-person testing; IC concepts were better understood by participants with more testing experience); iii) the role of website design on achieving IC (design of page to disrupt speedy click-throughs was valued and demonstrated seriousness of the consent page). Conclusions: Our careful attention to both content and design of the consent page of GCO was highly valued by potential users of the service, and effective in disrupting routinization of consent on websites. We argue that principles of IC apply equally in online self-testing programs as in clinical practice, and can be effectively achieved without detracting from the user experience.